Cognitive strategies oriented at inference processes in the development of students reading cycles v and vi basic education - Inga Arias, Miguel Gerardo (2014)
This investigation looking for to close a cycle of reading comprehension, because in previous jobs we already have demostrated that cognitive capacities was too fundamental specially en inferential capacity. The general objective propose lectures with the particular inferential strategies, which are a guarantee of reading comprehension. Consistent with this, the stated objectives are: a) Confirming the value of the strategies and the relevant procedures for the processing of information, which is essential for understanding and text production. b) Apply inference strategies in selected texts for students of V and VI Basic Education cycles. c) Propose reading modules with cognitive strategies aimed at inference processes to improve reading comprehension. What we expected was that students in the experimental groups, after application of the proposed modules, achieving greater development of their communicative abilities and language, which will be evidence of a strong reading comprehension. This research was supported by previous research which showed that the skills of inference correlate better with reading comprehension, therefore we wanted to validate modules reading strategies less to more complex, the cycles V (5 th and 6 th grade) and VI (1 st and 2 nd year of high school) in Basic Education. This research was supported by previous research which showed that the skills of inference correlate better with reading comprehension, therefore we wanted to validate modules reading strategies less to more complex, the cycles V (5th and 6th grade) and VI (1 and 2 secondary degrees) of the Basic Education for cognitive development factors, and also be curricular articulation axes between educational levels. Thus, we research to educational institutions representative. When we apply all the tools and strategies developed for this research and the development of the necessary analysis, we found that experimental group students behaved more efficient and effective reading comprehension in relation to group control. This research has validated modules that the school has developed to the level of workers and also gave us tools for the development of the module six (6) of the series of National Mobilization for Reading (MNCl) carried out the Ministry of Education (MINEDU). Therefore, we believe that this cycle of research has been very helpful and will allow better structuring of materials and activities for our students’ reading comprehension.